2018
DOI: 10.1093/humrep/dey276
|View full text |Cite
|
Sign up to set email alerts
|

Cell-lineage specificity of primary cilia during postnatal epididymal development

Abstract: Study funded by an NSERC operating grant to CB (RGPIN-2015-109194). No competing interest to declare.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 33 publications
3
17
0
Order By: Relevance
“…Arl mice have much longer astrocytic and neuronal primary cilia than wild type FVB/N and C57BL/6 mice Double transgenic Arl mice have become a useful mouse model to study primary cilia and centrosomes [33]. While this strain has been commonly used in developmental studies [33][34][35], little is known about their morphological features and cilia expression pattern in the mature mouse brain. To characterize cilia morphology of Arl mice, we first measured cilia length in the hippocampus.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Arl mice have much longer astrocytic and neuronal primary cilia than wild type FVB/N and C57BL/6 mice Double transgenic Arl mice have become a useful mouse model to study primary cilia and centrosomes [33]. While this strain has been commonly used in developmental studies [33][34][35], little is known about their morphological features and cilia expression pattern in the mature mouse brain. To characterize cilia morphology of Arl mice, we first measured cilia length in the hippocampus.…”
Section: Resultsmentioning
confidence: 99%
“…Arl mice contain fluorescent proteins that label Arl13bpositive primary cilia and Centrin2-positive centrosomes [33]. This strain has been used to investigate the roles of primary cilia in development [33][34][35]. We first found that overexpression of Arl13b significantly elongates both astrocyte and neuronal primary cilia in the hippocampus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the rete testis, the apical surface of the cuboidal epithelial cells bears a single long cilium—presumably a PC despite the lack of ultrastructural evidence—extending from a centriole pair (Fawcett & Dym, ; Dym, ). In the efferent ductules, the presence of multiple motile cilia and primary cilia‐like extensions has been reported to protrude from ciliated and non‐ciliated cells, respectively (Aire, ; Hess, ; Bernet et al ., ). While multiple motile cilia from the efferent ductules have recently been proposed to generate luminal flow turbulence to maintain sperm cells in suspension (Yuan et al ., ), the role of primary cilia in both the rete testis and the efferent ductules remains unknown.…”
Section: Diversity Of Cilia Found In the Male Reproductive Tractmentioning
confidence: 97%
“…Cilia are found throughout the male reproductive system as motile sperm flagella, multiple motile cilia (efferent ductules) (Ford et al ., ; Hess, ), and non‐motile sensory primary cilia (testis, rete testis, epididymis, and prostate) (Dym, ; Zhang et al ., ; Ou et al ., ; Dores et al ., ; Bernet et al ., ) (Table ). The broad diversity of ciliary extensions found at different stages of development confers to the male reproductive system a unique way to sense and control sperm function and spermatozoa surrounding environment.…”
Section: Diversity Of Cilia Found In the Male Reproductive Tractmentioning
confidence: 99%